Analisis Kadar Interferon Gamma pada Penderita TB - Fitriana, Eka; Simanjuntak, James P.; Hermansyah, Herry; Karneli, Karneli (Journal of Telenursing (JOTING), 2024)
This study aims to determine the levels of IFN-γ in patients with SO TB and RO TB and to analyze the differences in IFN-γ levels in patients with RO TB and SO TB. The research method used is descriptive-analytical with a cross-sectional approach. The results showed that of the 50 respondents with Pulmonary TB, the largest percentage of respondents were male (52%) and in the adult age category (44%). The examination results showed that the average IFN-γ level in patients with RO TB was lower, namely 65.38 pg/ml compared to the average IFN-γ level in patients with SO TB, namely 82.37 pg/ml. In conclusion, there is a significant difference between IFN-γ levels in patients with SO TB and RO TB. Keywords: Interferon Gamma, Drug-Resistant TB (RO TB)